Occupational Therapy for People with Early Parkinson’s Disease: A Retrospective Program Evaluation - Alan Sadural; Jillian MacDonald; Joelle Johnson; Kavita Gohil; Miriam Rafferty (Parkinson's Disease)
Purpose. Clinical practice guidelines establish that occupational therapy (OT) services are indicated for people with early Parkinson’s disease (PD). However, OT is uncommon compared to other rehabilitation services. This study describes the development and evaluation of a proactive, consultative OT program for people with early PD as a part of an integrated care approach. Materials and Methods. The program was developed by an occupational therapist adapting practice guidelines for people with early PD. Retrospective program evaluation occurred at an outpatient rehabilitation clinic. The consultative OT program for early PD includes a 90-minute evaluation with instruction in self-management techniques, individually tailored exercises, and follow-up recommendations. The program was evaluated with the RE-AIM framework. Postprogram semistructured interviews provided patient-reported program effectiveness and satisfaction. Results. In 2018, 23 individuals used OT out of 77 people with early PD who attended the proactive rehabilitation program. Most individuals (n = 16, 69.6%) were within Hoehn and Yahr stages 1-2 and were seen within 3 years of PD diagnosis. Participants presented with deficits in hand strength (60.0 ± 23.4 pounds) and dexterity (right hand 30.0 ± 8.0 seconds) and reported complaints about basic and/or instrumental activities of daily living (n = 15, 65.2%). Semistructured interviews (n = 16) revealed that most individuals (75%) reported high satisfaction. Of the 10 who recalled a home exercise program, 60% reported continued adherence. Consultative OT was delivered with fidelity in 22/23 individuals (96%). After one year, only two occupational therapists at one clinic had adopted the program, and the program is maintained in the organization. Conclusion. Occupational therapists reached people in the early stages of PD when a specific program was tailored to evaluate and target their specific needs. Motor activity deficits noted in individuals with early PD support future scaling and sustainability efforts of OT within this population. Quality improvement suggestions are discussed for future implementation and clinical trials.